PARTICIPATION OF PARENTS IN INCREASING CUSTOMER ORIENTATION OF PRESCHOOL EDUCATIONAL ORGANIZATIONS - Tursunboyeva Munirabonu Baxodirjon qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
To study the influence of parental behavior on business strategy in increasing the customer orientation of preschool educational organizations, preschool educational institutions establish partnerships with parents and children’s success in the educational system. they should develop mutual responsibility. In doing so, parental involvement is enhanced, parental efforts to support preschool organizations are encouraged, and they have a direct positive impact on a successful education system. Taking into account the importance of the participation of parents in the activities of preschool educational organizations, in this article we will analyze the impact of parental behavior on business strategy, the leading principles of successful cooperation between parents and preschool educational organizations are parenting, communication, We summarize the six factors of literacy, learning, decision-making, and community engagement, and six factors of advocacy, expertise, transfer, curriculum enrichment, consumerism, and collaboration. we will consider the models with the participation of parents. In addition, we draw conclusions and make recommendations on the impact of parental behavior on business strategy aimed at improving parental involvement.